Citizen science reveals waterfowl responses to extreme winter weather - Nicholas M. Masto; Orin J. Robinson; Michael G. Brasher; Allison C. Keever; Abigail G. Blake‐Bradshaw; Cory J. Highway; Jamie C. Feddersen; Heath M. Hagy; Douglas C. Osborne; Daniel L. Combs; Bradley S. Cohen (Global Change Biology, 2022)
Global climate change is increasing the frequency and severity of extreme climatic events (ECEs) which may be especially detrimental during late‐winter when many species are surviving on scarce resources. However, monitoring animal populations relative to ECEs is logistically challenging. Crowd‐sourced datasets may provide opportunity to monitor species' responses to short‐term chance phenomena such as ECEs. We used 14 years of eBird—a global citizen science initiative—to examine distribution changes for seven wintering waterfowl species across North America in response to recent extreme winter polar vortex disruptions. To validate inferences from eBird, we compared eBird distribution changes against locational data from 362 GPS‐tagged Mallards ( Anas platyrhynchos ) in the Mississippi Flyway. Distributional shifts between eBird and GPS‐tagged Mallards were similar following an ECE in February 2021. In general, the ECE affected continental waterfowl population distributions; however, responses were variable across species and flyways. Waterfowl distributions tended to stay near wintering latitudes or moved north at lesser distances compared with non‐ECE years, suggesting preparedness for spring migration was a stronger “pull” than extreme weather was a “push” pressure. Surprisingly, larger‐bodied waterfowl with grubbing foraging strategies (i.e., geese) delayed their northward range shift during ECE years, whereas smaller‐bodied ducks were less affected. Lastly, wetland obligate species shifted southward during ECE years. Collectively, these results suggest specialized foraging strategies likely related to resource limitations, but not body size, necessitate movement from extreme late‐winter weather in waterfowl. Our results demonstrate eBird's potential to monitor population‐level effects of weather events, especially severe ECEs. eBird and other crowd‐sourced datasets can be valuable to identify species which are adaptable or vulnerable to ECEs and thus, begin to inform conservation policy and management to combat negative effects of global climate change.